Implementasi Isbat Nikah Massal Di Madura: Kajian Sosiologis-Filosofis - Hasyim, Muh. Fathoni (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2019)
Marriage is a very important and sacred event in married life. Marriage is a legitimate starting point to establish kinship and brotherhood of the two extended families. So, it’s not uncommon for a wedding to be enlivened by a lively party, spending a very large budget. Nevertheless, there is a certain community in Madura that ignores it, so it does not record it in the official institution, the KUA (the Office of Religious Affairs). Even though marriage registration brings benefit, justice and protection of civil rights as well as preventive measures in preventing unawareness, so that the MWC NU of Gapura, Sumenep runs a program called “Mass Isbat Nikah”. The above problems raise two questions. Why do many isbat of marriage occur in a married couple? and how is the implementation? The review of this article will focus on how the implementation of mass marital marriage in Madura with socio-philosophical analysis. [ Pernikahan adalah peristiwa yang sangat penting dan sakral dalam kehidupan berumah tangga. Dari pernikahan itulah awal mula terjalinnya hubungan kekerabatan dan persaudaraan dua keluarga besar secara sah. Sehingga tidak jarang sebuah pernikahan dimeriahkan dengan pesta yang meriah, sehingga menghabiskan budget yang sangat besar. Meskipun demikian terdapat sebuah komunitas tertentu di Madura yang mengabaikannya, sehingga salah satu cara adalah dengan tidak mencatatkannya pada institusi resmi yaitu KUA. Padahal pencatatan pernikahan mendatangkan kemaslahatan, keadilan dan perlindungan terhadap hak-hak perdata serta sebagai tindakan preventif dalam mencegah kemadaratan, sehingga kondisi ini yang mendasari program kerja MWC NU di Kecamatan Gapura Kabupaten Sumenep untuk mengadakan “Isbat Nikah Massal”. Problematika di atas memunculkan dua pertanyaan yaitu Mengapa banyak terjadi isbat nikah pasangan suami istri di Madura serta bagaimana implementasinya? Kajian artikel ini akan difokuskan pada bagaimana implementasi isbat nikah massal di Madura dengan analisis sosio-filosofis.]